Pendampingan Pendidikan Agama pada SDN Balunglor 06 Balung di Tengah Pandemi Covid-19 - Nasirudin Al Ahsani; Izza Afkarina (Jurnal Al-Tatwir, 2021)
Education and teaching are not limited by circumstances, including in a pandemic like this. Since the Covid-19 pandemic has paralyzed the activities of the Indonesian people, it has greatly affected the course of educational activities. Education, which is a forum for the nation's next generation, in this very limited situation becomes a very big obstacle, not least the Teaching and Learning Activities experienced by elementary schools, precisely at SDN Balunglor 06 in Balung village. Teaching and learning activities were initially carried out in schools with a fairly effective time, the intended effectiveness was that the learning time and subject matter obtained by students was orderly and directed, now students and teachers are only allowed to take part in teaching and learning activities for only a few hours, students come to homeroom teacher as a location for teaching and learning activities. The purpose of this study was to determine the effectiveness of learning during the Covid-19 pandemic, to assist teaching and learning activities, as well as a form of teaching service from OFFDA KKN students. This service method uses the Asset Based Community Development (ABCD) method. The location of the service is at SND Balunglor 06 Balung Village, Jember Regency. Researchers have carried out observations and assisted in religious learning at SDN Balunglor 06. As a result of this service, the authors provided assistance in religious education and tried to inspire students' enthusiasm for learning by participating in teaching and learning activities at SDN Balunglor 06.